Analisis Studi Kasus Krisis Komunikasi PT. Alpen Food Industry (Aice Ice Cream) Dan Serikat Buruh - Raissa Regina; Arubay Mahardhikawatie; Indra Kusumawardhana (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2021)
PT. AFI or better known as the producer of AICE ice cream is a food sector company that is quite massive and well known by the public in Indonesia. The company with the tagline "Have an Aice Day" is quite popular in all Indonesians, from children to adults. A problem emerged in early 2017 which was felt by workers who were filled with labor demonstrations due to decreased wages, work accidents, working hours which resulted in poor relations between workers and management, not not due to a lack of good communication roles in management. In crisis communication, it is known as the Rhetoric Of Renewal (ROR) theory, which is a theory that emphasizes the positive values and characteristics of crisis communication, which emphasizes the future and restoring the image of the company. The focus of this theory is to help the parties affected by the crisis and planning carefully so that the organization and its stakeholders can be better in the future. ROR emphasizes on the future and recovery.